Federal Criminal Careers: an Empirical Examination of the Post-Conviction Risk Assessment (PCRA) - DeLisi, Matt (American journal of criminal justice, 2018)
The criminal career paradigm is a major research area but has largely overlooked federal offenders and federal data. Drawing on a population of federal supervised release clients in the Midwestern United States, the current study examined the predictive validity of the federal Post-Conviction Risk Assessment (PCRA) and its subscales for their association with six parameters of the criminal career. Poisson, negative binomial, and logistic regression models showed that PCRA Risk was significantly associated with annual offending rate (lambda), chronicity, prison misconduct, noncompliance on supervised release, having a warrant requested on supervised release, and career criminal status. Various PCRA subscales also were significantly associated with criminal career outcomes especially for current community supervision outcomes. These effects withstood confounding effects for age, sex, race, age of arrest onset, federal criminal history rank, and total prison exposure. The study supported basic criminal career findings using federal data and showed that a standard risk assessment actuarial in the federal system has utility as an indicator of the criminal career.